The Arab Gulf's pivot to Asia : from transactional to strategic partnerships - Janardhan, N. (Gulf studies., 2020)
Over the last two decades the relations between the countries of the Gulf and Asia have expanded beyond the economic domain to include political and even security arrangements. While oil and non-oil trade are still the fulcrum of their association, 'strategic' partnerships are fast becoming the norm. The contributors of this book argue that, along with economic diversification, the Gulf countries have also diversified their foreign policies, especially with China, India, Japan and South Korea, among others. Together with Russia, this could eventually alter the current US-centric security parad.